Dinamika Sosial-Ekonomi Masyarakat Multikultural Di Wilayah Perbatasan Sota Antara Masyarakat Adat Papua Dan Transmigran - Aviva Radja Najwa Amatullah; Rizky Aulia Sabrina Putri; Zulfayani; Rizya Amelia; Laeli Khusnaeni; Nurul Istiqomah (Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the dynamics of the lives of indigenous Papuan communities and transmigrants, particularly in the social and economic context of Sota Village, Merauke Regency, South Papua. The study uses a qualitative approach with semi-structured interviews, documentation, and focus group discussions (FGDs). This study involved various parties to obtain a comprehensive view of the social interaction between indigenous peoples and transmigrants. Data were obtained through interviews with leaders and indigenous peoples of Sota Village. The results of the study show that the social relationship between indigenous peoples and transmigrants is harmonious, characterized by cooperation in social activities, mutual assistance, and joint economic development. The presence of transmigrants has had a positive impact on improving welfare, equalizing infrastructure, and introducing modern agricultural techniques to indigenous peoples. On the other hand, local wisdom such as Adat Sasi also plays a role in maintaining social harmony and ecological balance, while the traditional deliberation mechanism serves as a means of peaceful conflict resolution. Indigenous communities show openness to change but remain critical of the sustainability of the transmigration program due to land limitations. Overall, this study concludes that multicultural life in Sota reflects the success of social integration based on the values of tolerance, mutual respect, and cooperation in building a peaceful and sustainable society.